Biological Characteristics of Grass Carp (Ctenopharyngodon Idella) and Silver Carp (Hypophthalmichthys Molitrix) In The Zarafshan River - ugli, Buvrayev; qizi, Tolibova; qizi, Bolqiboyeva (Jurnal Biologi, 2025)
This article analyzes the biological characteristics of the white amur (Ctenopharyngodon idella) and white humphead (Hypophthalmichthys molitrix) fish living in the Zarafshan River. The article discusses the taxonomy, morphological characteristics, growth process, reproductive biology and role of both species in water bodies. Based on studies conducted in the Zarafshan River area, the ecological adaptation of these fish species and their contribution to the composition of the ichthyofauna are shown. These species play an important role in the development of fisheries and are useful in maintaining the ecological balance.